A survey on the acceptance of unattended trains. (March 2023) - Morast, Albrecht; Voß, Gudrun M.I.; Dautzenberg, Pia S.C.; Urban, Peter; Nießen, Nils
Abstract: Due to increasing prices, growing environmental awareness, and resource scarcity, railway operations become increasingly more important. In today's conventional railway operations drivers are needed for driving trains. Drivers have a very responsible job to drive the trains safely. However, they work differently depending on the time of day. Due to illness and strikes, train journeys had to be cancelled in the past. Therefore, a driver takes a special role in today's railway operations. The operation in metros is different. Due to different system properties, unattended metro systems correspond the state of the art. In the future, technical developments will enable unattended operations on railway to substitute drivers, too. Although promising, several challenges need to be accomplished for a successful market launch of unattended trains. Next to several technical challenges, this could especially concern the acceptance among potential users. If a technology or a system is not accepted, it will most likely not be adopted. Most empirical literature regarding the acceptance of driverless or unattended vehicles is related to road and air, but not to railway transport. In this paper, we, therefore, present the results of an online survey that investigated the acceptance of unattended trains. The results of the survey indicate that people generally accept unattended trains. Numerous participants would use such trains. Furthermore, some sociodemographic factors, age, current usage of rail transport, and prior experience with unattended trains, affect the acceptance. However, the results show that people worry about cyberattacks. Overall, the implementation of unattended railway trains seems to be promising. This is an important finding for railway companies to drive the trend towards unattended trains. Highlights: Most studies regarding the acceptance of unattended vehicles are related to road and air, but not to railway transport. The questionnaire is based, among other things, on Osswald's Car Technology Acceptance Model. We identified influencing factors, which seem to impact the acceptance of unattended trains. People generally accept unattended trains. A further important result is that people worry about cyberattacks.